Kinematics and kinetics of left and right legs during landing of grand jeté performed by professional ballet dancers - Kuromaru, A. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
INTRODUCTION: Ballet dancers are required to use the same technique on both sides of the body, though humans have each characteristic movement as seen in dominant foot manner. It is supposed that there are characteristics of movement control unique to ballet dancers. Although a difference between left and right ground reaction forces was observed in ballet students` landing of a grand jeté, a basic ballet jump (1), there have been few kinematic and kinematic studies between left and right professional ballet dancers` ones. The purpose of this study was to compare kinematics and kinetics of those left and right grand jeté landings performed by professional ballet dancers.